2014
DOI: 10.11646/zootaxa.3816.1.1
|View full text |Cite
|
Sign up to set email alerts
|

<p><strong>Ticks of Australia. The species that infest domestic animals and humans</strong></p>

Abstract: The book Australian Ticks by F.H.S. Roberts (1970) is a land-mark in Australian tick biology. But it is time for a new and improved book on the ticks of Australia. The present book has identification guides and accounts of the biology and diseases associated with the 16 species of ticks that may feed on domestic animals and humans in Australia. These comprise five argasid (soft) ticks: Argas persicus (poultry tick), Argas robertsi (Robert's bird tick), Ornithodoros capensis (seabird soft tick), O. gurneyi (kan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
270
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(283 citation statements)
references
References 0 publications
1
270
0
Order By: Relevance
“…Further work is warranted to test this hypothesis with heterologous and homologous challenge infestations to the Bm86 variants associated with reduced vaccine efficacy. (Barker and Walker 2014;Walker et al 2003) collectively prompted comparison of ticks from this investigation to the re-described morphological features of these closely related species (Table 3). According to the available criteria, these comparisons indicated that the female ticks, the source of Bm86 transcript sequences used for this work, were morphologically consistent with R.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Further work is warranted to test this hypothesis with heterologous and homologous challenge infestations to the Bm86 variants associated with reduced vaccine efficacy. (Barker and Walker 2014;Walker et al 2003) collectively prompted comparison of ticks from this investigation to the re-described morphological features of these closely related species (Table 3). According to the available criteria, these comparisons indicated that the female ticks, the source of Bm86 transcript sequences used for this work, were morphologically consistent with R.…”
Section: Resultsmentioning
confidence: 88%
“…(B.) australis were compared to female and male ticks collected in this study (Barker and Walker 2014;Estrada-Pena et al 2012;Walker et al 2003).…”
Section: Tick Samplesmentioning
confidence: 95%
“…Ticks collected from dogs in six remote Aboriginal communities were also included in the present study (Walgett, NSW; Lake Nash, Mutitjulu, Tennant Creek, Yuendumu, NT; Kurrangki, WA; Supplementary Table 1). All ticks were stored in 70% ethanol until required and were identified morphologically using standard keys (Barker and Walker, 2014).…”
Section: Sample Collectionmentioning
confidence: 99%
“…Ticks were placed in 70 % ethanol immediately after removal from hosts or collection from the environment and stored at 4 C until molecular analysis. Ticks were morphologically identified into species, instar and sex using standard keys (Roberts, 1970;Barker & Walker, 2014).…”
Section: Tick Collectionmentioning
confidence: 99%
“…Ixodes holocyclus is endemic to eastern Australia and is one of the most significant Australian native arthropods from both a medical and veterinary perspective (Barker & Walker, 2014). This is due to its high affinity for parasitizing humans and domestic animals, its high prevalence in densely populated regions of Australia, its ability to cause life-threatening paralysis in domestic animals, and weakness, paralysis, dermatological reactions, mammalian meat allergies and to transmit infections of Rickettsia spp.…”
Section: Phylogenetic Analysismentioning
confidence: 99%